Serous microcystic adenoma (glycogen rich cystadenoma) of the pancreas - Jacob Sunitha; Rawat Premeeta; Mark Ruth (Wolters Kluwer Medknow Publications, 2010)
Serous microcystic adenoma (SMCA) is a rare pancreatic tumor with a striking predilection for elderly females and a rather unique morphology. Classically, the tumor is riddled with innumerable small cysts around a stellate scar. The quintessential histological features are closely placed small cysts lined by glycogen rich cuboidal epithelium. In view of its excellent prognostic outcome, this tumor needs to be accurately diagnosed. This report documents a case of SMCA occurring in a 60-year-old female.